(untitled) (Journal of actual problems of jurisprudence, 2019)
Criminal law fight against criminal encroachment against sexual inviolability sexual freedom of the individual, ensuring the rights and legitimate interests of citizens in the field of sexual relationship is one of the urgent tasks facing the bodies of investigation and inquiry.